(untitled) (AL-FIKRAH: Jurnal Kajian Islam, 2024)
This study examines the use of makruh water for purification from the perspectives of the Shafi’i and Hambali schools of thought. Makruh water refers to water that is not recommended for use if other permissible (mubah) water is available. The aim of this research is to understand the various categories of makruh water according to these two schools and their implications for the purification practices of Muslims. The methodology used is library research, which involves collecting and analyzing data from various classical and modern literature related to Islamic law. The results of this study indicate that the use of sacred water which is makruh for purification, according to the perspectives of the Shafi’i and Hambali schools of thought, is deemed makruh. The contribution of this study is to provide a deeper understanding of the use of makruh water in the context of purification and its legal implications according to the two major schools of thought in Islam.